Pengaruh Kompetensi Karyawan dan Beban Kerja Terhadap Stres Kerja dan Dampaknya Terhadap Turnover Intention pada PT. XYZ - Ayu Lestari Santi; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
The objective of this study id to analysis the effect of the employee competence, workload on work stress and its impact on turnover intention at PT. XYZ. This study used quantitative method by distributing questionnaires to 120 employees. Sampling technique used nonprobability sampling (saturation sampling). The sampling technique is nonprobability (saturated sample). Analysis in this study used classical assumption test consist of the normality test, heteroskesdaticity test, and multicollinearity test, and multiple linear regression test, t test, F test, and determination analysis. Hypothesis test (t test) result that shows that the variable employee competency variables do not affect work stress. Workload affects work stress. Employee competency and workload affect work stress. And work stress that affects turnover intention.